Development of Mobile-Based Learning Media to Improve Creative Thinking Abilities and Learning Interest of Middle School Students - Permatasari, Ambar Gini; Nurjanah, Nurjanah; Andrian, Rian (Pedagonal : Jurnal Ilmiah Pendidikan, 2024)
Mathematics, a compulsory subject from elementary school, is essential for developing critical thinking, reasoning, creative thinking, communication and collaboration. However, the ability mentioned above in Indonesian students is still low, as evidenced by the results of PISA and TIMSS. The 4C capabilities, which consist of Critical Thinking, Reasoning, Creative Thinking, Communication, and Collaboration, are very important for 21st century learning. To improve the ability to think creatively, it is necessary to have an innovation that has an impact on student learning outcomes, one of which is through learning media. Geometry, a popular subject in junior high school mathematics, poses challenges for students. This study to improve creative thinking skills and geometry learning media, researchers developed mobile-based geometry learning media using the ADDIE model. The process of developing mobile-based geometry learning media is carried out through the stages of analysis, design, development, implementation and evaluation. Learning using learning media that has been developed is classified as effective. Students can master the material presented in learning using mobile-based geometry learning media.